Social assistance in Turkey: an overview of seven social assistance and solidarity foundations - Zağralı Tunç, Fatma Nur. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2017)
The main aim of the thesis is to scrutinize the coexistence of two different social assistance understandings in Turkey observed through the Social Assistance and Solidarity Foundations (SYDV) of seven districts. On the one hand, there is a rights-based assistance, which is tax-based, regular, in-cash, and relies on transparent rules. Contrary to this, a charity-based assistance is a system that relies on personal benevolence and is irregular in time sequences and in amounts, is predominantly granted in-kind, and has discretion in rules. The trends observed in the budgetary data of SYDVs are analyzed with regard to population size and the socioeconomic standards of the districts to account for variations along with the dichotomy in social assistance understanding. The study argues that there is a positive correlation between socioeconomic characteristics, district population, and the understanding of social assistance they have, without establishing a causal link. In order to explain the dichotomy in social assistance understandings, I propose the hypothesis that as the competition between the incumbent and the opposition party becomes stronger in a district, higher irregular social assistance amounts are allocated to the district in order to increase the likelihood of electoral victory by the ruling party. Using most similar systems design, I compare data on election results and irregular social assistance from Ümraniye and Küçükçekmece, and find support for the hypothesis.
Keywords: Solidarity -- Political aspects -- Turkey.